2017
DOI: 10.1021/jacs.7b07479
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Selective Cholesterol Decorated Macrocyclic Transmembrane Ion Carriers

Abstract: Anion transporters play a vital role in cellular processes and their dysregulation leads to a range of diseases such as cystic fibrosis, Bartter's syndrome and epilepsy. Synthetic chloride transporters are known to induce apoptosis in cancer cell lines. Herein, we report triamide macrocycles that are easily synthesized and externally functionalized by pendant membrane-permeable groups. Among a variety of chains appended onto the macrocycle scaffold, cholesterol is found to be the best with an EC value of 0.44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…46 It is also possible that the more lipophilic cations can aggregate in the membrane or even partly precipitate from solution, thus lowering anion transport. [47][48][49] A B C To verify our interpretation that these cations behave as mobile fluoride ion carriers, we tested the transport properties of [3] + and [7] + by using DPPC-based vesicles (DPPC = 1,2-dipalmitoyl-sn-glycero-3-phosphtidylcholine) (Figure 6C). This phospholipid is known to form temperature sensitive bilayers that undergo a phase transition between a gel and a liquid at 41 C. 48,49 It has been previously suggested that channel-type transporters are less affected by this phase transition.…”
Section: Figure 4 Schematic Representation Of Selected Anion-transport Experiments Showing An Idealized Eypc Unilamellar Vesiclementioning
confidence: 99%
See 1 more Smart Citation
“…46 It is also possible that the more lipophilic cations can aggregate in the membrane or even partly precipitate from solution, thus lowering anion transport. [47][48][49] A B C To verify our interpretation that these cations behave as mobile fluoride ion carriers, we tested the transport properties of [3] + and [7] + by using DPPC-based vesicles (DPPC = 1,2-dipalmitoyl-sn-glycero-3-phosphtidylcholine) (Figure 6C). This phospholipid is known to form temperature sensitive bilayers that undergo a phase transition between a gel and a liquid at 41 C. 48,49 It has been previously suggested that channel-type transporters are less affected by this phase transition.…”
Section: Figure 4 Schematic Representation Of Selected Anion-transport Experiments Showing An Idealized Eypc Unilamellar Vesiclementioning
confidence: 99%
“…[47][48][49] A B C To verify our interpretation that these cations behave as mobile fluoride ion carriers, we tested the transport properties of [3] + and [7] + by using DPPC-based vesicles (DPPC = 1,2-dipalmitoyl-sn-glycero-3-phosphtidylcholine) (Figure 6C). This phospholipid is known to form temperature sensitive bilayers that undergo a phase transition between a gel and a liquid at 41 C. 48,49 It has been previously suggested that channel-type transporters are less affected by this phase transition. 50 However, in the case of [3] + and [7] + , we observed a drastic decrease in transport when the temperature of the assay was lowered from 45 C to 25 C, indicating that transport is significantly affected by the fluidity of the bilayer.…”
Section: Figure 4 Schematic Representation Of Selected Anion-transport Experiments Showing An Idealized Eypc Unilamellar Vesiclementioning
confidence: 99%
“…[5] A plug-and-select scaffold, wherein the ion selectivity can be precisely tuned by changing the ion-binding motif is highly desirable for therapeutic applications. Our group has developed a variety of acyclic [6] and macrocyclic [7] scaffolds for transporting cation, and anions, respectively. Our studies with the acyclic scaffolds [8] have led us to propose a simple alanine derived tripeptide scaffold with a selectivity inducing unit at the C terminus as a potential universal scaffold (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Ion channels form pores for ions to pass through the membranes, whereas mobile carriers bind with anions and diffuse across the membranes. Therefore, ion transport efficiency of mobile carriers strongly depends on the membrane fluidity since diffusion is restricted in the membranes with low fluidity, while ion channels are not significantly affected, as transmembrane diffusion is less important [25–27] . Thus influence of the membrane fluidity was investigated using 1,2‐dipalmitoyl‐ sn ‐glycero‐3‐phosphocholine (DPPC) instead of DOPC for HPTS assay.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ion transport efficiency of mobile carriers strongly depends on the membrane fluidity since diffusion is restricted in the membranes with low fluidity, while ion channels are not significantly affected, as transmembrane diffusion is less important. [25][26][27] Thus influence of the membrane fluidity was investigated using 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) instead of DOPC for HPTS assay. DPPC adopts highly fluid liquid phase above the phase transition temperature (T m = 41°C), and much less fluid gel phase below T m .…”
Section: Mechanism Of Ion Transport By Imamentioning
confidence: 99%